2019
DOI: 10.1093/mnras/stz483
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the asteroid–neutron star collision model for the repeating fast radio bursts

Abstract: The origin of fast radio bursts (FRBs) is still a mystery. One model proposed to interpret the only known repeating object, FRB 121102, is that the radio emission is generated from asteroids colliding with a highly magnetized neutron star (NS). With N -body simulations, we model a debris disc around a central star with an eccentric orbit intruding NS. As the NS approaches the first periastron passage, most of the comets are scattered away rather than being accreted by the NS. To match the observed FRB rate, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 159 publications
(188 reference statements)
0
19
1
Order By: Relevance
“…Levison et al 1997) we note that the orbit of Jupiter is only ∼ 20 times wider than the orbit assumed here and therefore the (angular) density of asteroids does not need to be larger if the swarms span a similar angular size. This contrasts with the simulations carried out by Smallwood et al (2019) in the context of the colliding asteroid model (Dai et al 2016), which showed that an asteroid belt with a density several orders of magnitude larger than that of the solar system's main belt or Kuiper's belt was necessary for that model.…”
Section: Number Of Asteroidscontrasting
confidence: 66%
See 2 more Smart Citations
“…Levison et al 1997) we note that the orbit of Jupiter is only ∼ 20 times wider than the orbit assumed here and therefore the (angular) density of asteroids does not need to be larger if the swarms span a similar angular size. This contrasts with the simulations carried out by Smallwood et al (2019) in the context of the colliding asteroid model (Dai et al 2016), which showed that an asteroid belt with a density several orders of magnitude larger than that of the solar system's main belt or Kuiper's belt was necessary for that model.…”
Section: Number Of Asteroidscontrasting
confidence: 66%
“…In the orbiting asteroid model, the periodicity of activity windows is due to the specific orbital dynamics of the system. This is also the case for a number of other models: Decoene et al (2020) which is also based on the Alfvén wing mechanism, Smallwood et al (2019); Dai & Zhong (2020) for colliding asteroids, Gu et al (2020) for accreted white-dwarf companions, and Lyutikov et al (2020) for either magnetospheric or wind magnetar models. In magnetospheric magnetar models, it has also been proposed that free precession of the neutron star (Zanazzi & Lai 2020;Levin et al 2020), or ultra-long period magnetars (Beniamini et al 2020) might be the cause.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Fast radio bursts can be produced if asteroids pass close to the Roche limit of a compact object with an electromagnetic wind (Mottez & Zarka 2014;, or if they undergo collisions with this object (Dai 2016;Smallwood et al 2019). The infall of asteroids from standard belts onto the central compact object can be triggered by Kozai-Lidov oscillations, in the presence of an outer black hole.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In particular, via the Alfvén wing emission mechanism presented in Mottez & Zarka (2014), this emission could be the source of FRBs. Other authors have proposed that FRBs result from the impact of asteroids and comets on central compact objects (Geng & Huang 2015;Dai 2016;Smallwood et al 2019). Interestingly, the above models could naturally lead to repeating signals, as long as small bodies, such as asteroids, pass by the star at a rate corresponding to the observations.…”
Section: Introductionmentioning
confidence: 97%